Penerapan Program Amaliyah Tadris Untuk Meningkatkan Kompetensi Siswa dalam Mengajar Kelas XI di MAN 5 Jombang - Rosidah Rosidah; Khoirul Umam (Jurnal Budi Pekerti Agama Islam, 2026)
Amaliyah tadris or teaching practice is an activity in the form of teaching practice carried out by someone in a guided manner to acquire skills in giving lessons and taken within a certain time as one of the requirements for fulfilling the program. Amaliyah tadris is an important program that is taught to students to improve student competence in order to become professional teachers, and as a provision to prepare for the delivery of their knowledge to students or the public, especially in terms of education. Based on the problems above, this study has 3 objectives related to the research focus of the Implementation of the Amaliyah Tadris Program to Improve Student Competence in Teaching Class XI at MAN 5 Jombang. The research objectives are 1) to describe and explain the implementation of the amaliyah tadris program at Madrasah Aliyah Negeri 5 Jombang. 2) To describe and explain efforts to improve student competence in teaching at Madrasah Aliyah Negeri 5 Jombang. 3) To describe and explain the supporting and inhibiting factors for implementing the amaliyah tadris program to improve student competence in teaching Class XI at Madrasah Aliyah Negeri 5 Jombang. The type of research used in this research is field research. The research was conducted using a qualitative approach with descriptive methods. Data collection was carried out using interviews, observation techniques, and documentation. Informants in this study consisted of Deputy Head of Student Affairs, Head of the Amaliyah Tadris Program, Madrasah Teachers where the Amaliyah Tadris program was implemented, Students. The data collected for observation and interviews were analyzed using data source triangulation analysis techniques. Based on the results of the study it was found that: Micro teaching at MAN 5 Jombang is packaged in the form of the Amaliyah Tadris program or teaching practice. For this program conceptualized by group division. Each group consists of 8 members and is placed in 18 TPQ Institutions. Placement at the TPQ institution also has conditions with a distance of 5-7 km from MAN 5 Jombang.